2012
DOI: 10.1007/s00397-012-0630-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity, phase behavior, and rheology of polypropylene/polystyrene blends with multi-walled carbon nanotube

Abstract: The electrical, rheological properties and phase change behavior of polypropylene (PP)/ polystyrene (PS) blends filled with multi-walled carbon nanotube (MWNT) were investigated. Two kinds of masterbatch were used to prepare ternary blends of PP, PS, and MWNT, and the effects of the kinds of masterbatch were confirmed by phase morphology of ternary blends and the distribution of MWNT. From thermodynamic analysis, MWNT is expected to locate in PS phase and it shows a good agreement with the TEM observations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Figure illustrates the variation of G ′ with the angular frequency for the PS/CB, PS/CB, and PS/EVA/CB blends. All of the composites presented gradual increases in G ′ as the amount of CB increased, and this behavior was more important at low frequencies and indicated the development of the CB network with increasing filler content . It was possible to observe a significant increase in G ′ between the unloaded systems and those containing only 2% CB; this suggested that the filler network structure started to form in this CB content range.…”
Section: Resultsmentioning
confidence: 87%
“…Figure illustrates the variation of G ′ with the angular frequency for the PS/CB, PS/CB, and PS/EVA/CB blends. All of the composites presented gradual increases in G ′ as the amount of CB increased, and this behavior was more important at low frequencies and indicated the development of the CB network with increasing filler content . It was possible to observe a significant increase in G ′ between the unloaded systems and those containing only 2% CB; this suggested that the filler network structure started to form in this CB content range.…”
Section: Resultsmentioning
confidence: 87%
“…This change in morphology may be related to the variation of the viscosity of the phase where the CNT is preferentially localized. Moreover, if the filler is localized at the interface, the chance of coalescence should decrease thus contributing for the formation of more elongated structures under shear stress, during melt mixing …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, conducting composites based on this polymer can find potential applications in electronic components and equipments, which requires some specific characteristics, including EMI shielding and antistatic properties. Some reports have been discussed the effect of CNT, as well as, processing conditions on the morphology and electrical properties of PS blends containing polypropylene, low‐density polyethylene, or PVDF as the second blend component.…”
Section: Introductionmentioning
confidence: 99%
“…By choosing a blend composition whose phase containing the percolated conductive filler is continuous or a blend with co-continuous structure, the amount of required conductive filler for attaining the insulator-conducting transition (percolation threshold) is usually lower that that employed in single polymer matrix. This phenomenon is known as double percolation and has been reported for several CNT-loaded thermoplastic binary blends, including acrylonitrile-butadienestyrene (ABS) copolymers with PA6 (Poyekar et al, 2014(Poyekar et al, , 2015a, ABS/ polycarbonate (PC) (Xiong et al, 2013), poly(Llactide) (PLA)/(EVA) (Shi et al, 2013), PS/PP (Hwang et al, 2012), PS/PE (Patra et al, 2015), PS/polyvinylidene fluoride (PVDF) (Ren et al, 2017), PS/EVA (Soares et al, 2018), and PS/PLA (Nasti et al, 2016).…”
Section: Introductionmentioning
confidence: 84%